A Multicenter Pilot Randomized Clinical Trial of a Home-Based Exercise Program for Patients With Cirrhosis: The Strength Training Intervention (STRIVE). (23rd April 2021) - Lai, Jennifer C.; Dodge, Jennifer L.; Kappus, Matthew R.; Wong, Randi; Mohamad, Yara; Segev, Dorry L.; McAdams-DeMarco, Mara
Abstract : INTRODUCTION: We developed the strength training intervention (STRIVE), a home-based exercise program targeting physical function in patients with cirrhosis. In this pilot study, we aimed to evaluate the safety and efficacy of STRIVE. METHODS: Eligible were adult patients with cirrhosis at 3 sites. Patients were randomized 2:1–12 weeks of STRIVE, a 30-minute strength training video plus a health coach or standard of care (SOC). Physical function and quality of life were assessed using the Liver Frailty Index (LFI) and Chronic Liver Disease Questionnaire (CLDQ), respectively. RESULTS: Fifty-eight and 25 were randomized to STRIVE and SOC arms, respectively: 43% women, median age was 61 years, MELDNa, Model for End-Stage Liver Disease Sodium was 14, and 54% were Child-Pugh B/C. Baseline characteristics were similar in the STRIVE vs SOC arms except for rates of hepatic encephalopathy (19 vs 36%). LFI @ 12 weeks was available in 43 STRIVE and 20 SOC participants. After 12 weeks, the median LFI improved from 3.8 to 3.6 (ΔLFI −0.1) in the STRIVE arm and 3.7 to 3.6 (ΔLFI −0.1) in the SOC arm ( P = 0.65 for ΔLFI difference). CLDQ scores improved from 4.6 to 5.2 in STRIVE participants (ΔCLDQ 0.38) and did not change in SOC participants (4.2–4.2; ΔCLDQ −0.03) ( P = 0.09 for ΔCLDQ difference). One patient died (SOC arm) of bleeding. Only 14% of STRIVE participants adhered to the strength training video for 10–12 weeks. No adverse events were reported by STRIVE participants. DISCUSSION: STRIVE, a home-based structured exercise program for patients with cirrhosis, was safely administered at 3 sites, but adherence was low. Although all participants showed minimal improvement in the LFI, STRIVE was associated with a substantial improvement in quality of life.